2005
DOI: 10.1299/kikaib.71.1978
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Development of Coherent Structure in a Plane Jet (2nd Report, Spatio-temporal Velocity Structure by the Combined Analysis of KL Expnasion and Fourier Transform)

Abstract: The simultaneous measurement of the velocities at two points with X-type hot wire probes has been performed in three different downstream regions of a plane jet (the potential core region, the interaction region and the self-preserving region). By applying Karhunen-Lò eve (KL) expansion in space and time, the structure development of the plane jet is investigated from a viewpoint of both space and frequency. From the downstream variation of the eigenfunctions, it is found that in the early stage of the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These frequencies are almost consistent with the frequency of the flapping motion investigated by Gotari et al [6]. In addition, the eigenspectra for the 1 st mode are relatively more similar to those for the 1 st v (crossstreamwise velocity fluctuation) mode than those for the 1 st u (streamwise velocity fluctuation) mode obtained in the previous study [18] but they are not completely consistent with those for the streamwise or cross-streamwise velocity fluctuations.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…These frequencies are almost consistent with the frequency of the flapping motion investigated by Gotari et al [6]. In addition, the eigenspectra for the 1 st mode are relatively more similar to those for the 1 st v (crossstreamwise velocity fluctuation) mode than those for the 1 st u (streamwise velocity fluctuation) mode obtained in the previous study [18] but they are not completely consistent with those for the streamwise or cross-streamwise velocity fluctuations.…”
Section: Resultssupporting
confidence: 86%
“…Figure 6 shows the downstream variation of the eigenspectra for the 1 st mode obtained with reference to the previous study [18], where each eigenspectrum is normalized by the sum of frequency integrals of eigenspectra over all modes. Figure 6 indicates that the spectra have small peaks at x/d = 10 and 20, whose frequencies are 120 Hz and 45 Hz, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 (a) include the small fluctuations, but the large fluctuation is dominant as a whole. Secondly, the coefficients of middlenumbered modes (the 7th mode a (7) u and the 9th mode a (9) u ) in Fig. 9 (b) are almost random signals.…”
Section: Eigenfunctionsmentioning
confidence: 96%
“…It was found that the Kelvin-Helmholtz instability appeared first when the jet lost its stability, and then with the increasing of the nonlinear effects, the secondary instability appeared and the streamwise vortices formed. Recently, Sakai et al [10,11] used hot wire probe and proper orthogonal decomposition (POD) to study the characteristics of coherent structures in different regions in the plane jet. They used the eigenvalues and eigenfunctions as well as the spatial velocity correlations to characterize the development of coherent structures and found that the characteristics of coherent structures could be identified by the reconstructed two-point spatial velocity correlation.…”
mentioning
confidence: 99%